124 Correlating structure and function to better identify surrogate end points for clinical trial design: a longitudinal clinical and imaging study of primary progressive aphasia. (29th July 2019) - Mahoney, Colin
Abstract : Introduction: Measuring longitudinal change in white matter tracts offers a highly sensitive way of monitoring the course of a range of neurodegenerative conditions. However, it remains unclear how structural changes correlate with symptom progression. Clinically meaningful outcomes remain a key requirement in therapeutic trial design so imaging biomarkers need to accurately predict these outcomes. Identifying surrogate clinical end points is of particular importance in neurodegenerative conditions where clinical change evolves slowly. To address this the current study aims to identify potential surrogate end points by assessing correlations between clinical and neuroimaging measures. Methods: 30 patients meeting consensus criteria for a diagnosis of primary progressive aphasia underwent longitudinal imaging and neuropsychological assessments at baseline and one year. A mixed effects model was designed to test for significant interactions over time between changes in neuropsychological performance and Fractional Anisotropy (FA) in key white matter tracts. Results: Declining single word comprehension correlated with reducing FA within bilateral inferior longitudinal fasciculus (ILF), bilateral superior longitudinal fasciculus (SLF) and the genu of the corpus callosum; declining naming ability correlated with reducing FA in the left ILF, right uncinate fasciculus and right SLF; declining word repetition correlated with reducing FA within the left ILF. Conclusions: Declining neuropsychological scores correlated with longitudinal decline in FA in a number of white matter tracts across an anatomically distributed language network. Correlations between function and structure provide evidence that monitoring structural white matter changes in the tracks identified may have value as a surrogate end point for future clinical trials.